2022
DOI: 10.1111/joss.12734
|View full text |Cite
|
Sign up to set email alerts
|

Kefir with artificial and natural dyes: Assessment of consumer knowledge, attitude, and emotional profile using emojis

Abstract: The consumers' perception and emotional profile (using emojis) about different dyes labeled in kefir packages were evaluated. The products were natural (KN, nonflavored, and without dye), and acerola-flavored with artificial dye (KCA), natural dye (KCN), or acerola-residue dye (KCR). Furthermore, the consumer's knowledge and attitudes about dyes were evaluated. KN, KCN, and KCR showed higher perceived acceptability, healthiness, security, and purchase intent than KCA and were associated with positive emoji. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…When comparing products with the same acceptability, the emotional profile may aid in differentiation, and this is a trendy topic in sensory science [139]. Emotional profiling of dairy products by different methods was reported in other studies [140][141][142][143]; however, products similar to those in our study were not evaluated in the previous studies.…”
Section: Verall Acceptability and Induced Emotions For The Judges Of ...mentioning
confidence: 56%
“…When comparing products with the same acceptability, the emotional profile may aid in differentiation, and this is a trendy topic in sensory science [139]. Emotional profiling of dairy products by different methods was reported in other studies [140][141][142][143]; however, products similar to those in our study were not evaluated in the previous studies.…”
Section: Verall Acceptability and Induced Emotions For The Judges Of ...mentioning
confidence: 56%
“…Their use as an alternative for synthetic colorants has been extensively researched on a large scale. For example, Penna et al [ 177 ] found that consumers positively perceived the natural dyes used in kefir, while they had a negative perception regarding artificial colors since they believed that kefir manufactured with natural colorants is healthier and tastier. Similarly, Galetovic and colleagues [ 178 ] studied the role of PBPs in the amelioration of the sensory test scores of skim milk.…”
Section: Economic Valorization Of Pbps From Microalgaementioning
confidence: 99%
“…However, compared with natural colorants, the use of artificial colorants is limited by the relatively greater risks associated with their consumption [5]. In fact, artificial colorants have a certain toxicity and are associated with numerous pathologies [5], which is of great concern to consumers [6]. This situation justifies the importance of food controls and inspections based on standards, whose development and constant revision require factual data for risk analysis.…”
Section: Introductionmentioning
confidence: 99%